Internalisasi Pendidikan Multikultural di SMP Pancabudi Medan - Dirgahayu, Wini; Hanum, Azizah (Al-Wasathiyah: Journal of Islamic Studies, 2024)
This research aims to analyze the process of internalizing multicultural education at Pancabudi Middle School, Medan. This school is known as an A-accredited private educational institution which is committed to producing a generation of excellence, noble character and global insight. The research method used is qualitative with data collection techniques through observation, interviews and documentation. The research results show that multicultural education at Pancabudi Middle School is internalized through three main aspects, namely intracurricular, extracurricular and special programs. In the extracurricular aspect, diversity values ​​are integrated into the curriculum through subjects such as Civics and History Education, as well as interactive learning methods. In the extracurricular aspect, students gain direct experience of diversity through arts and culture activities, scouts and social programs. In addition, special programs such as Culture Week and Diversity Day are designed to strengthen appreciation for differences among students. Multicultural education is also applied in everyday life through the creation of an inclusive environment, as well as instilling the values ​​of tolerance and communication ethics. In conclusion, a comprehensive approach in internalizing multicultural education at Pancabudi Medan Middle School has succeeded in creating a learning atmosphere that supports diversity and strengthens student character. In this way, the goals of multicultural education can be achieved as a whole.